2010
DOI: 10.1002/maco.201005819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacterial exopolymers on cell adhesion of Desulfovibrio vulgaris on high alloyed steel: Corrosion inhibition by extracellular polymeric substances (EPS)

Abstract: Extracellular polymeric substances (EPS) were studied with regard to their potential application as inhibitors of biocorrosion. EPS that have been isolated from biofilms of sulphate-reducing bacteria (SRB) were adsorbed on samples of high alloyed steel (type 1.4301) at different temperatures. The samples were exposed to SRB containing solution and afterwards analysed by fluorescence microscopy (FM). The results show that the EPS form an incomplete layer and lead to a smaller amount of cell adhesion when compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 68 publications
0
16
0
2
Order By: Relevance
“…Bacterial cells on 316L were typical rod‐shaped bacterial cells mostly forming patches of colonies on the surface. The formation of typical biofilms (cells embedded in self‐produced extrapolymeric substance (EPS)) was not evident. It was noted that bacterial cells on 316L exposed to raw seawater differed in size and fluorescence to cells attached to coupons exposed to treated seawater which can be related to some inhibition effects by residual chemical treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial cells on 316L were typical rod‐shaped bacterial cells mostly forming patches of colonies on the surface. The formation of typical biofilms (cells embedded in self‐produced extrapolymeric substance (EPS)) was not evident. It was noted that bacterial cells on 316L exposed to raw seawater differed in size and fluorescence to cells attached to coupons exposed to treated seawater which can be related to some inhibition effects by residual chemical treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the family Rhodospirillaceae within the class Alphaproteobacteria were previously found in oil facilities and biofilms (15,68), and like Pseudomonas and Desulfovibrio species (18,53,69), these Alphaproteobacteria could contribute to biofilm formation by polysaccharide production, for example (Fig. 4) (68).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, recent studies showed that using the EPS, separated from the microbes, could reduce corrosion by SRB (Stadler et al, 2008(Stadler et al, , 2010Finkenstadt et al, 2011). This corrosion protection by EPS appeared to be species dependent.…”
Section: Metal Corrosion Inhibition Using Microbially Based Techniquesmentioning
confidence: 96%